Supporting Elements in the Learning Process through E-Learning Training at SMAN 2 Boyolali - Ekarini, Fitria; Sukamta, Sri; Arief, Ulfah Mediaty; Ananda, Bella Risky; Shofiani, Diah; Oktiagi, Radiva Hera (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2020)
One positive impact of technological development on education is providing facilities to support the learning and teaching process. The teachers to be more efficient, and the delivery of material can be easily conveyed through e-learning facilities. Schoology is an e-hearing media platform with various facilities that make it easy for educators and students in the educational process to academic results. The purpose of this activity is to test the usability level of using Schoology. The administration and teaching process to go to the level of understanding of operations through community service carried out at SMAN 2 Boyolali. Pre-test results that indicate that the high school has not yet implemented a learning management system. There are 5.26% of teachers who are only limited to learning the e-learning Schoology, while 94.74% only know it through the Universitas Negeri Semarang team. After the training, the results of the post-test show that 80.26% of teachers can use Schoology. The existence of e-learning training can help teachers support the teaching and learning process at school.